The impact of lower gas and oil prices on global gas and LNG markets - Howard V. Rogers (The Oxford Institute for Energy Studies, 2015)
Regional gas price trends post 2008 – Supply and demand trends – Russian price : volume strategy in the European market – Contract price formation for future LNG projects to Asia – Global gas dynamics post 2015 – Summary and conclusions
Keywords: 330; Gaspreis; Erdgasmarkt; Flüssiggas; Welt